PESAN KOMUNIKASI TARI ABUANG DI DESA PAKRAMAN TENGANAN PEGRINGSINGAN KECAMATAN MANGGIS KABUPATEN KARANGASEM - Pramesti Dasih, I Gusti Ayu Ratna (Institut Hindu Dharma Denpasar, 2018)
Communication message is a material that is conveyed to others in the form of ideas both verbally and nonverbally, to express certain intentions according to the needs of others regarding their benefits and needs. Message is a set of meaningful symbols conveyed by communicators. The message can be in the form of ideas or opinions that have been formulated in the form and symbol of communication forwarded to the communicant. The message should have a core message or theme as an influence to change communicant attitudes and behavior. Communication message in the performance of Abuang Dance in Pakraman Village, Tenganan Pegringsingan, is contained in the character of Satyam-Siwam-Sundaram. Satyam-Siwam-Sundaram is a concept of Hindu teachings namely the concept of truth, holiness and beauty. The communication message of Abuang Dance is also a form of offerings and beliefs to enhance the sraddha bhakti community of Pakraman Tenganan Pegringsingan Village to Ida Sang Hyang Widhi Wasa. Through the performance of Abuang Dance, it can strengthen kinship because it is a form of deviation from the ancestors of the Pakraman Tenganan Pegringsingan Village, so that they can be given peace of mind and no time.